Production of Cypripedium montanum seedlings for commercial value and reintroduction into restoration projects: phase II - Smith, Roger; Smith, Jane; Liebler, Scott (Lankesteriana: International Journal on Orchidology, 2015)
The mountain lady’s slipper (Cypripedium mon- tanum Douglas ex Lindl. is a large and charismatic perennial orchid once widely distributed in montane regions of the northwestern United States. This native North American orchid is a member of a genus that has been highly prized by collectors worldwide. Cypripedium is now among the most endangered plant genera in the world. As evidence of threats to its survival, a decade ago